Optimalisasi Kegiatan Praktikum Melalui Penggunaan Modul Penuntun Praktikum Berbasis Virtual Lab - Sirait, Jeliana Veronika; Kartika Putri, Aprilia; Fiardilla, Fauziah (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2025)
The implementation of practical activities is very much needed in science education, especially physics material. Almost all physics materials require practical activities. The limitations of practical tools and materials and the ability of educators are major challenges in implementing practical activities. The results of interviews with Physics Education students showed that practical activities were carried out with simple tools and had not fully used the practical guidance module. Students were confused about the procedures for implementing practical activities so they needed a practical guidance module. This community service activity was carried out with the aim of optimizing practical activities through the use of a virtual lab-based practical guidance module. This activity was attended by Physics Education students as prospective users of the practical guidance module. The entire series of activities went smoothly, students were enthusiastic about following from the beginning to the end of the activity. This can be seen from the positive response of students. To evaluate the response, a questionnaire was given, students agreed that this module made it easier for them to carry out virtual lab-based practical activities. This activity also increased students' insight in developing virtual practical activities and compiling a guidance module equipped with a practical implementation tutorial.